2021
DOI: 10.1016/j.csbj.2021.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the molecular basis of age and gender differences in outcomes of SARS-CoV-2 infections

Abstract: Graphical abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 91 publications
2
36
0
Order By: Relevance
“…Patients with dementia have multiple comorbidities such as diabetes and pneumonia, higher baseline inflammation and limited capacity to follow protective recommendations, factors that could explain this result 28 . Our results are consistent with the importance of age and sex in COVID-19 infection 3 , 4 , 22 , 29 ; the study of such repeatable and straightforward variables that are accessible to health professionals and policy-makers could help to develop sex-balance and age-adaptive guidelines 29 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Patients with dementia have multiple comorbidities such as diabetes and pneumonia, higher baseline inflammation and limited capacity to follow protective recommendations, factors that could explain this result 28 . Our results are consistent with the importance of age and sex in COVID-19 infection 3 , 4 , 22 , 29 ; the study of such repeatable and straightforward variables that are accessible to health professionals and policy-makers could help to develop sex-balance and age-adaptive guidelines 29 .…”
Section: Discussionsupporting
confidence: 88%
“…The results of our work are consistent with previous studies highlighting the importance of chronic systemic inflammation on COVID-19 severity 11 . The association between chronic inflammation status and infection severity has also been described at molecular level, especially in aging 21 , 22 . The existence of low levels of HMGA1 gene may play a key role as a risk factor for COVID-19 patients by triggering inflammatory pathways and atherosclerosis 22 , 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 Growing evidence suggested that HMGA2 may be associated with tumorigenesis in a variety of cancers, including lung, breast, kidney and gastric cancers. 8 , 9 , 11 , 19 In our present study, we identified HMGA2 as a down‐stream target of miR‐103a, and our data revealed that miR‐103a directly regulate the expression of HMGA2. These data suggested that SNHG1 promoted RCC proliferation through upregulated HMGA2 by sponging miR‐103a.…”
Section: Discussionsupporting
confidence: 58%
“…Meanwhile, the level of DNMT1 was found significantly downregulated in SARS-COV-2–infected epithelial cells ( Muhammad et al, 2021 ). SARS-COV-2 infection mainly affects the molecular mechanisms of aging centered on HMGA1 and HMGA2 proteins, and their interactions may impair or trigger inflammatory pathways, leading to various responses in different age groups ( Mercatelli et al, 2021 ). To conclude, DNMT1, HMGA1, and HMGA2 might be central TFs in the TF–gene regulatory network in COVID-19/NSCLC.…”
Section: Discussionmentioning
confidence: 99%